FAKTOR-FAKTOR YANG MEMPENGARUHI PERUSAHAAN MELAKUKAN AUDITOR SWITCHING (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2015-2016) - Khalimatus Sa’adah; Andi Kartika (Faculty of Economic and Business Universitas STIKUBANK, 2018)
This research has a purpose to analizze the influence of the size of Public Accounting Firm (KAP), the size of client companies, financial distress, a management changes and audit opinion on was auditor switching. Auditor switching is a dislplacement behavior by a company auditoras a result of auditor rotasion mandatory or voluntary. The type of data which is used in this research is secondary data, that was audited report of service company listed in Indonesia Stock Exchange on 2014-2016 period. Sample was purposive sampling method. Samples were 56 companies from 143 companies listed in Indonesia Stock Exchange in 2014-2016, so that the research data was analyzed totaled 168. Data analyze technique which is used in this research is logistic regression analysis. The results indicate that the size of Public Accounting Firm (KAP), the size of client companies, financial distress, and audit opinion do not effect to auditor switching. A management change effect positif to auditor switching. Keyword : auditor switching, the size of public accounting firm (kap), the size of client companies, financial distress, a management changes and audit opinion.